Knowledge Transmission and Kyai-Santri Network in Pesantren in Java Island During the 20th Century: A Study on Popongan Manuscript - Gusmian, Islah; Abdullah, Mustaffa (Afkar: Jurnal Akidah dan Pemikiran Islam, 2022)
The article examined the knowledge transmission and the network of kyai-santri in pesantren in Java in the 20th century. Both of these aspects were studied through Popongan manuscripts kept at Popongan Pesantren, Klaten, Central Java. The Popongan manuscript was derived from the study notes and a copy of the text referenced in the study at the pesantren. A large number of manuscripts were written and copied by Kyai Muhammad Muqri, one of the kyai at Popongan Pesantren. Through this study, Popongan manuscripts were positioned as social and cultural products, so that interactions, social relationships, and interests in them can be properly expressed. The research showed that the fields of knowledge studied in pesantren were diverse, including fiqh, grammar, theology, Sufism, and history. This diverse field of knowledge was well transmitted through kyai-santri networks. In addition, the kyai also criticized religious views that were inconsistent with Islamic principles. For example, the rejection of Wahhabi’s teachings by Muḥammad Dimyaṭī in the book Lawāmi‘ al-Burhān. In terms of socio-culture, this study also revealed that through knowledge, the relationship between kyai-santri as well as between kyai-rulers in Surakarta was interconnected from time to time. Through this kind of education, pesantren played an important role in building a comprehensive religious tradition.